Study of the protective effect of dexamethasone on cisplatin-induced ototoxicity in rats - Capelo,Isabelle Oliveira Jatai (2017)
Abstract Purpose: To evaluate the ability of dexamethasone to protect against cisplatin (CDDP)-induced ototoxicity. Methods: Male Wistar rats were divided into the following three groups: 1) Control (C): 6 animals received intraperitoneal (IP) saline solution, 8 ml/kg/day for four days; 2) C + CDDP: 11 animals received 8 ml/kg/day of IP saline and, 90 min after saline administration, 8 mg/kg/day of IP CDDP for four days; and 3) DEXA15 + CDDP: 11 animals received IP dexamethasone 15 mg/kg/day and, 90 min after dexamethasone administration, received 8 mg/kg/day of IP CDDP for four days. Results: It was found that dexamethasone did not protect against weight loss in CDDP-exposed animals. The mortality rate was comparable with that previously reported in the literature. The auditory threshold of animals in the DEXA15 + CDDP group was not significantly altered after exposure to CDDP. The stria vascularis of animals in the DEXA15 + CDDP group was partially preserved after CDDP exposure. Conclusions: Dexamethasone at the dose of 15 mg/kg/day partially protected against CDDP-induced ototoxicity, based on functional evaluation by brainstem evoked response audiontry (BERA) and morphological evaluation by optical microscopy. However, dexamethasone did not protect against systemic toxicity.